Extrusion of sorghum grain and soybeans for lactating sows - Mills, C.G.; Gugle, Terry L.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred-seventeen primiparous sows were used to determine the effects of extruded sorghum grain and soybeans in lactation diets on sow and litter performance. The sows were fed a sorghum-soybean-based diet with the sorghum and soybeans extruded either singly or together. Treatments were: 1) ground sorghum-soybean meal (SBM)-soy oil-based control; 2) extruded sorghum-SBM-soy oil; 3) ground sorghum-extruded soybeans; and 4) sorghum and extruded soybeans blended then extruded together (extruded blend). All diets were formulated to .80% lysine, .90% Ca, .80% P, and 1.47 Mcal ME/lb. Sows fed diets with extruded ingredients tended to wean more pigs with greater survivability and greater litter weight gains compared to sows fed the ground sorghum-SBM-based control diet. No differences occurred in sow weight or sow backfat loss. Sows fed extruded soybeans had decreased sow weight loss (14.6 vs 29.7 lb) compared with those fed extruded sorghum. Overall, improvements in litter weight gain were 6, 7, and 10% for extruded sorghum, extruded soybeans, and the extruded blend, respectively, when compared to the ground sorghum- SBM-soy oil-based control. In conclusion, our data indicate that extrusion of ingredients for lactation diets improves sow and litter performance, and the greatest improvements were obtained by extrusion of blended soybeans and sorghum grain.
Keywords: Swine; Process; Extrusion; Sorghum; Sows; Lactation